Neutronic simulation of medical radioisotope 99Mo and 177Lu production in IPR 14 MeV neutron generator facility. (May 2023) - Swami, H.L.; Saxena, A.; Vala, S.; Abhangi, M.; Kumar, Ratnesh; Kumar, Rajesh
Abstract: An accelerator based 14 MeV neutron generator is commissioned at Institute for Plasma Research India. The generator is based on the linear accelerator concept where the deuterium ion beam impinged to the tritium target to produce neutrons. The generator is designed to produce 1 × 10 12 neutrons per sec. The 14 MeV neutron source facilities are an emerging tool for the lab scale experiments and research. In order to utilize the generator for the welfare of humanity, the assessment is made for the production of medical radioisotopes using the neutron facility. The usage of radioisotopes in the treatment and diagnosis of a disease is an important factor in the healthcare sector. A series of calculations are conducted to generate radioisotopes, especially 99 Mo and 177 Lu those are having huge applications in the medical and pharmaceutical industries. 99 Mo can be also generated through neutron reactions 98 Mo(n, g) 99 Mo and 100 Mo(n, 2n) 99 Mo apart from fission reaction. The cross section of 98 Mo(n, g) 99 Mo is high in the thermal energy range whereas 100 Mo(n, 2n) 99 Mo occurs at a high energy range. 177 Lu can be produced using the reactions 176 Lu (n, g) 177 Lu and 176 Yb (n, g) 177 Yb. The cross section of both 177 Lu production routes is higher at thermal energy range. The neutron flux level near the target is around 10 10  cm −2 s −1 . In order to enhance production capabilities, the neutron energy spectrum moderators are used to thermalize the neutrons. The materials used as a moderator are beryllium, HDPE, graphite, etc. Moderators enhance the capabilities of medical isotope production in neutron generators. Highlights: The breeding route and production of 99 Mo and 177 Lu isotopes in the 14 MeV neutron generator facility have been explored here. The facility is having neutron yield of 10 12 s -1 and can deliver the fluence of 10 15 cm -2 in continuous operation. The maximum breeding of 1.14 Ci/day of 99 Mo can be achieved using the moderators. It can be further increased by enriching the 98 Mo in MoO3, it reaches 2.8 Ci/day. The 177 Lu breeding is also simulated with moderators, it is around 0.3 Ci.